2017
DOI: 10.1136/bjophthalmol-2017-310890
|View full text |Cite
|
Sign up to set email alerts
|

Orbital trapdoor fractures: different clinical profiles between adult and paediatric patients

Abstract: Fracture pattern, type of incarcerated tissue and incidence of hypoesthesia of the infraorbital nerve were different between adult and paediatric patients. Adult patients had a larger preoperative BSVF and less need for surgical reduction; however, there was less improvement in postoperative BSVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
1
27
1
1
Order By: Relevance
“…Pojedyncza szczelina złamania przebiega poprzecznie albo podłużnie przez dno oczodołu. Wzdłuż przebiegu szczeliny dochodzi do uwięźnięcia tkanek bez powstania przepukliny oczodołowej [1,[19][20][21][22].…”
Section: Złamanie Typu En Clapet -Taką Postać Opisaliunclassified
See 1 more Smart Citation
“…Pojedyncza szczelina złamania przebiega poprzecznie albo podłużnie przez dno oczodołu. Wzdłuż przebiegu szczeliny dochodzi do uwięźnięcia tkanek bez powstania przepukliny oczodołowej [1,[19][20][21][22].…”
Section: Złamanie Typu En Clapet -Taką Postać Opisaliunclassified
“…A single fracture gap extends transversely or longitudinally across the orbital floor. Tissue lodging occurs along the gap, however no orbital hernia is observed [1,[19][20][21][22].…”
Section: Materiał I Metodymentioning
confidence: 99%
“…Diplopia is a common sign of orbital fracture, especially medial fracture pattern due to rectus muscle entrapment [13]. Infraorbital nerve hypoesthesia is a symptom of orbital fracture especially when the infraorbital rim is involved [14]. Subconjunctival hemorrhage and periorbital ecchymosis are useful signs of an underlying orbital fracture [15] (Figure 9).…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Orbital fractures often cause transient neurosensory disturbance of the infraorbital nerve (ION), and reported rates vary between 11% and 35% depending on the site and type of orbital fracture. [1][2][3] Retrospective studies have reported that long-term neurosensory disturbance persists in 9.3% -55% of patients who have had orbital operations. [2][3][4] At worst, chronic pain may develop in the ION, which can result in problems in daily life, clinical depression, and the need for antidepressant medication.…”
Section: Introductionmentioning
confidence: 99%